Strategi Pemerolehan Kosakata Bahasa Indonesia pada Siswa Kelas Rendah Sekolah Dasar - Sintya Imelda Simangunsong; Deswita Maharani; Silvina Noviyanti; Sariani; Rian Sahputra (STKIP Subang, 2026)
Vocabulary acquisition is a crucial foundation for lower-grade elementary school students to build communication and literacy skills. This study aims to identify and analyze vocabulary acquisition strategies in elementary school-aged children through a literature review. The research method used is library research, analyzing data from various scientific journals and textbooks related to children's language development. The results show that vocabulary acquisition in lower-grade students is influenced by biological, cognitive, and social environmental factors. Effective strategies include the targeted use of digital educational media such as YouTube, intensive social interaction, and stimulation through a language-rich learning environment. The conclusion of this study is that the synergy between the roles of teachers, parents, and the use of technology is the main key to optimizing students' vocabulary during this critical developmental period.